EKSISTENSI HUKUM ISLAM DI INDONESIA DALAM PEMBANGUNAN NASIONAL - Hendra Gunawan (Yurisprudentia: Jurnal Hukum Ekonomi, 2018)
Islamic law brought by the prophet Muhammad, popularized by jargon “wama arsalnaka ila rahmatan lil'alamin” (not the message of Islam was revealed, but for the benefit of the entire universe) that govern the lives of Muslims in particular and mankind in general correspond to Islam derived its name from "salam" which means safety, means to bring salvation to the whole entire universe without exception, including for the people of Indonesia. But lately, Islam as if identified with terrorists, radicals, and fully impressed with the spread of violence in the media, the author makes the heart sad, move from here the author would like to see the existence of Islamic law in Indonesia in national development as a consolation. In this paper, the author tries to decipher how the development of Islamic law in Indonesia, how Islamic law is applied in Indonesia, and how the contribution of Islamic law to undermine national development. Authors see Islamic law in Indonesia of legislation used in a religious court, a compilation of Islamic law, qanun province of Nanggroe Aceh Darussalam, and fatwas Majelis Ulama Indonesia, from here the authors see sumbangsi-sumbangsi Islamic law to the acceleration of national development both directly or indirectly. As it turned out, the existence of Islamic law in the course of the Indonesian nation can not be disputed, ranging from pre-independence, post-independence, and until today. One of them Law No. 1 Year 1974 On marriage according to Islamic Law and Presidential Decree No. 1 Year 1991 About the Compilation of Islamic Law are both contributing to increased security, peace, public order and Indonesia. Then, Act. No. 23 Year 2011 on the Management of Zakat to help the government address poverty. Lastly, the Act. No. 21 Year 2008 regarding Islamic Banking in line with national development goals to improve the lives of the people, the fact that Islamic Banking is growing rapidly and the demand of Indonesian society